2016
DOI: 10.3389/fpsyg.2016.00907
|View full text |Cite
|
Sign up to set email alerts
|

Action Video Game Training for Healthy Adults: A Meta-Analytic Study

Abstract: Action video game (AVG) has attracted increasing attention from both the public and from researchers. More and more studies found video game training improved a variety of cognitive functions. However, it remains controversial whether healthy adults can benefit from AVG training, and whether young and older adults benefit similarly from AVG training. In the present study, we aimed to quantitatively assess the AVG training effect on the cognitive ability of adults and to compare the training effects on young an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 101 publications
4
119
2
2
Order By: Relevance
“…Interventions. In all, 34 reviews reported meta-analytic results for cognitive training (Table 1), covering a variety of cognitive training approaches, including computerized training Hill et al, 2017;Hoefler, 2016;Lampit, Hallock, & Valenzuela, 2014;Shao et al, 2015;Tetlow & Edwards, 2017), memory training (das Nair, Cogger, Worthington, & Lincoln, 2016;Floyd & Scogin, 1997;Gross et al, 2012;Hudes, Rich, Troyer, Yusupov, & Vandermorris, 2019;Martin et al, 2011;Metternich et al, 2010), working memory training (Melby-Lervag & Hulme, 2016; Weicker, Villringer, & Thone-Otto, 2016) and videogames (Toril, Reales, & Ballesteros, 2014;P. Wang et al, 2016).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Interventions. In all, 34 reviews reported meta-analytic results for cognitive training (Table 1), covering a variety of cognitive training approaches, including computerized training Hill et al, 2017;Hoefler, 2016;Lampit, Hallock, & Valenzuela, 2014;Shao et al, 2015;Tetlow & Edwards, 2017), memory training (das Nair, Cogger, Worthington, & Lincoln, 2016;Floyd & Scogin, 1997;Gross et al, 2012;Hudes, Rich, Troyer, Yusupov, & Vandermorris, 2019;Martin et al, 2011;Metternich et al, 2010), working memory training (Melby-Lervag & Hulme, 2016; Weicker, Villringer, & Thone-Otto, 2016) and videogames (Toril, Reales, & Ballesteros, 2014;P. Wang et al, 2016).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…). Attempts to systematically determine whether playing AVGs benefits cognitive performance via meta‐analytic approaches have documented a consistent cognitive benefit in quasiexperimental studies . In short, individuals who report playing 3 or more hours per week of action video games, and having done so for at least the past 6 months, outperform individuals classified as NVGPs on a wide variety of cognitive tasks.…”
Section: The Influence Of Video Game Play On Cognition and Its Neuralmentioning
confidence: 99%
“…Attempts to systematically determine whether playing AVGs benefits cognitive performance via meta-analytic approaches have documented a consistent cognitive benefit in quasiexperimental studies. 60,[64][65][66][67][68][69][70] In short, individuals who report playing 3 or more hours per week of action video games, and having done so for at least the past 6 months, outperform individuals classified as NVGPs on a wide variety of cognitive tasks. However, as discussed above, whether AVGPs perform better on these cognitive tasks because they play action video games, or whether they chose to play action video games because they excel at this type of game play from the get-go, can only be answered through intervention studies.…”
Section: The Influence Of Video Game Play On Cognition and Its Neuralmentioning
confidence: 99%
“…In all, 34 reviews reported meta-analytical results for CT (Table 1), covering a variety of CT approaches, including computerized training (Gates, Rutjes, et al, 2019;Gates, Vernooij, et al, 2019;Hill et al, 2017;Hoefler, 2016 Wang et al, 2016). Three reviews focused on CS (C. Cooper et al, 2012;Kim et al, 2017;Woods et al, 2012).…”
Section: Interventionsmentioning
confidence: 99%